ANALISIS DAMPAK BULLYING TERHADAP PERILAKU EMOSIONAL SISWA DI UPT SD NEGERI 013 GANTING - Annisa, Aulia; Yandri Kusuma, Yanti; Fitra Surya, Yenni; Aprinawati, Iis; Fadhilaturrahmi, Fadhilaturrahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the impact of bullying on the emotional behavior of fourth-grade students at the UPT SD Negeri 013 Ganting. The research focuses on the impact of verbal, nonverbal, and physical bullying on students' emotional behavior. This study uses a qualitative method and a case study approach, with data collection techniques through interviews, observation, and documentation. The research subjects consisted of the homeroom teacher, one student who was a victim of bullying, and the victim's parents. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. Research shows that verbal bullying, such as teasing, insulting, and slandering, can lead to decreased self-confidence, feelings of shame, depression, and social withdrawal. Nonverbal bullying, such as threats, awkward behavior, and manipulative behavior, can lead to feelings of fear, anger, and discomfort in the classroom. Meanwhile, physical bullying, such as hitting and kicking, can cause victims to feel pain, trauma, and a reluctance to go to school. They may also exhibit changes in emotional behavior, such as becoming withdrawn and easily irritated. Overall, bullying significantly impacts students' emotional behavior, including decreased motivation to learn, feelings of depression, and difficulties socializing.